Pengaruh PENGARUH WORD OF MOUTH TERHADAP NIAT BERKUNJUNG DAN DAMPAKNYA TERHADAP KEPUTUSAN BERKUNJUNG LAGI - Kharisma, Pande Maha; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen; Vol 10 No 12 (2021)DO - 10.24843/EJMUNUD.2021.v10.i12.p11, 2021)
The purpose of this study is to find out the influence of word of mouth to visit the intention and the impact it has on the decision to visit again. The study was conducted at Nefatari Villas with a sample of 30 respondents. The population sampled in this study was visitors staying at Nefatari Villas. Data collection method using questionnaire, with sampling technique used is purposive sampling. Data analysis techniques used are descriptive statistical analysis and inferential analysis thas is SEM PLS with the help of Warp PLS. The results of this study word of mouth positively and significantly influence the intention of visiting tourists in Nefatari Villas, word of mouth has a positive and significant effect on the decision to visit again tourists at Nefatari Villas, Intention to visit positively and significantly on the decision to visit again tourists at Nefatari Villas. Keywords : word of mouth, intention to visit, decision to visit again.